Serological Testing for COVID-19, Immunological Surveillance, and Exploration of Protective Antibodies - Peroni, Luis A.; Toscaro, Jessica M.; Canateli, Camila; Tonoli, Celisa C. C.; de Olivera, Renata R.; Benedetti, Celso E.; Coimbra, Lais D.; Pereira, Alexandre Borin; Marques, Rafael E.; Proença-Modena, José L.; Lima, Gabriel C.; Viana, Renata; et al. (Frontiers in Immunology, 2021)
Serological testing is a powerful tool in epidemiological studies for understanding viral circulation, and assessing the effectiveness of virus control measures, as is the case of SARS-CoV-2, the pathogenic agent of COVID-19. Immunoassays can quantitatively reveal the concentration of antiviral antibodies. The assessment of antiviral antibody titers may provide information on virus exposure, and changes in IgG levels, is also an indicative of a reduction in viral circulation. In this work, we describe a serological study for the evaluation of antiviral IgG and IgM antibodies and their correlation with antiviral activity. The serological assay for IgG detection used two SARS-CoV-2 proteins as antigens, the nucleocapsid N protein and the 3CL protease. Cross-reactivity tests in animals have shown high selectivity for detection of antiviral antibodies, using both the N and 3CL antigens. Using samples of human serum from individuals previously diagnosed by PCR for COVID-19, we observed high sensitivity of the ELISA assay. Serological results with human samples also suggest that the combination of higher titers of antiviral IgG antibodies to different antigen targets may be associated with greater neutralization activity, which can be enhanced in the presence of antiviral IgM antibodies.